2020
DOI: 10.31234/osf.io/84nve
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Age Differences in Memory Formation on Neural Mechanisms of Consolidation and Retrieval

Abstract: Episodic memory decline is a hallmark of cognitive aging and a multifaceted phenomenon. We review studies that target age differences across different memory processing stages, i.e., from encoding to retrieval. The available evidence cumulates in the proposition that older adults form memories of lower quality than younger adults, which has negative downstream consequences for later processing stages. We argue that low memory quality in combination with age-related neural decline of key regions of the episodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 147 publications
(206 reference statements)
0
4
0
Order By: Relevance
“…Developmental differences in memory abilities are accompanied by age-dependent changes in the underlying brain structures and functions during maturation and senescence (Li et al, 2004; Ofen and Shing, 2013; Sander et al, 2020a; Shing et al, 2010; Van Petten, 2004). Specifically, functional differences during encoding may influence the specificity of mnemonic contents and may thus account for performance differences across the lifespan (Bowman et al, 2019; Fandakova et al, 2019; Morcom, 2015; Park et al, 2013; Sander et al, 2020b). In line with this, studies measuring neural specificity as the discriminability of BOLD activation patterns have shown a positive relation between the specificity of these patterns during encoding and memory performance in young and older adults (Kobelt et al, 2020; Koen et al, 2019) as well as in children (aged 7–12 years, (Fandakova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Developmental differences in memory abilities are accompanied by age-dependent changes in the underlying brain structures and functions during maturation and senescence (Li et al, 2004; Ofen and Shing, 2013; Sander et al, 2020a; Shing et al, 2010; Van Petten, 2004). Specifically, functional differences during encoding may influence the specificity of mnemonic contents and may thus account for performance differences across the lifespan (Bowman et al, 2019; Fandakova et al, 2019; Morcom, 2015; Park et al, 2013; Sander et al, 2020b). In line with this, studies measuring neural specificity as the discriminability of BOLD activation patterns have shown a positive relation between the specificity of these patterns during encoding and memory performance in young and older adults (Kobelt et al, 2020; Koen et al, 2019) as well as in children (aged 7–12 years, (Fandakova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There was no time limit for answering. Given the known age differences in learning rates and limitations between younger and older individuals, we adjusted for task difficulty between age groups (Sander et al, 2021). Specifically, the older adults took a test every time they learned a block, whereas the younger adults took a test every two blocks.…”
Section: Methodsmentioning
confidence: 99%
“…One of the cognitive domains most vulnerable to age-related deterioration is episodic memory [2][3][4] , the long-term memory that enables us to recollect the spatio-temporal, perceptual, and emotional details that constitute a prior experience 5,6 . Growing evidence suggests a critical component of age-related episodic memory loss to be reduced quality and specificity with which information can be encoded into and retrieved from memory [7][8][9][10] . Recent behavioural studies employing continuous measures of memory performance have demonstrated that even when able to successfully retrieve similar amounts of information about a past event as younger adults, the fidelity, or precision, of the retrieved memories is impoverished in older age 9,11,12 , with such reductions appearing to at least partly arise from differences during longterm memory retrieval 9 .…”
Section: Introductionmentioning
confidence: 99%